Open Access

A note on the higher-order Frobenius-Euler polynomials and Sheffer sequences

Advances in Difference Equations20132013:41

https://doi.org/10.1186/1687-1847-2013-41

Received: 9 December 2012

Accepted: 6 February 2013

Published: 21 February 2013

Abstract

In this paper, we investigate some properties of polynomials related to Sheffer sequences. Finally, we derive some identities of higher-order Frobenius-Euler polynomials.

1 Introduction

Let λ ( 1 ) C . The higher-order Frobenius-Euler polynomials are defined by the generating function to be
( 1 λ e t λ ) α e x t = e H ( α ) ( x | λ ) t = n = 0 H n ( α ) ( x | λ ) t n n ! (see [1–17])
(1)

with the usual convention about replacing ( H ( α ) ( x | λ ) ) n by H n ( α ) ( x | λ ) . In the special case, x = 0 , H n ( α ) ( 0 | λ ) = H n ( α ) ( λ ) are called the n th Frobenius-Euler numbers of order α ( R ).

From (1) we have
H n ( α ) ( x | λ ) = l = 0 n ( n l ) H n l ( α ) ( λ ) x l = l = 0 n ( n l ) H n l ( α ) ( λ ) x n l (see [6]) .
(2)
By (2) we get
x H n ( α ) ( x | λ ) = n H n 1 ( α ) ( x | λ ) , H n ( 0 ) ( x | λ ) = x n for  n Z + .
(3)
It is not difficult to show that
H n ( α ) ( x + 1 | λ ) λ H n ( α ) ( x | λ ) = ( 1 λ ) H n ( α 1 ) ( x | λ ) (see [1–17]) .
(4)
Let us define the λ-difference operator λ as follows:
λ f ( x ) = f ( x + 1 ) λ f ( x ) .
(5)
From (5) we can derive the following equation:
λ n f ( x ) = λ λ n - times f ( x ) = k = 0 n ( n k ) ( λ ) n k f ( x + k ) = k = 0 n ( n k ) ( λ ) k f ( x + n k ) .
(6)
As is well known, the Stirling numbers S ( l , n ) of the second kind are defined by the generating function to be
( e t 1 ) n = n ! l = 0 S ( l , n ) t l l ! (see [5, 6, 11])
(7)
and
( e t 1 ) n = l = 0 ( m = 0 n ( n m ) ( 1 ) n m m l ) t l l ! .
(8)
By (7) and (8), we get
S ( l , n ) = 1 n ! m = 0 n ( n m ) ( 1 ) n m m l = n 0 l n ! (see [11]) ,
(9)

where f ( x ) = f ( x + 1 ) f ( x ) .

Now, we consider the λ-analogue of the Stirling numbers of the second kind as follows:
( e t λ ) n = n ! l = 0 S ( l , n | λ ) t l l !
(10)
and
( e t λ ) n = l = 0 ( m = 0 n ( n m ) ( λ ) n m m l ) t l l ! .
(11)
From (10) and (11), we have
S ( l , n | λ ) = 1 n ! m = 0 n ( n m ) ( λ ) n m m l = 1 n ! λ n 0 l
(12)
and
S ( l , n | λ ) = 0 for  n > l .
(13)
From (4) and (5), we have
λ H n ( α ) ( x | λ ) = ( 1 λ ) H n ( α 1 ) ( x | λ ) .
(14)
Let be the set of all formal power series in the variable t over with
F = { f ( t ) = n = 0 a k k ! t k | a k C } .
indicates the algebra of polynomials in the variable x over , and P is the vector space of all linear functionals on (see [5, 11]). In [11], L | p ( x ) denotes the action of the linear functional L on a polynomial p ( x ) , and we remind that the vector space structure on P is defined by
L + M | p ( x ) = L | p ( x ) + M | p ( x ) , c L | p ( x ) = c L | p ( x ) ,

where c is a complex constant.

The formal power series
f ( t ) = k = 0 a k k ! t k F
(15)
defines a linear functional on by setting
f ( t ) | x n = a n for all  n Z +  (see [11]) .
(16)
From (15) and (16), we have
t k | x n = n ! δ n , k (see [5, 11]) .
(17)
Let f L ( t ) = k = 0 L | x k k ! t k . From (17) we have
f L ( t ) | x n = L | x n for all  n Z + .
(18)

By (18) we get L = f L ( t ) . It is known in [11] that the map L f L ( t ) is a vector space isomorphism from P onto . Henceforth, will denote both the algebra of formal power series in t and the vector space of all linear functionals on , and so an element f ( t ) of will be thought of as both a formal power series and a linear functional. We will call the umbral algebra. The umbral calculus is the study of umbral algebra (see [5, 11]).

The order O ( f ( t ) ) of the nonzero power series f ( t ) is the smallest integer k for which the coefficient of t k does not vanish. A series f ( t ) has O ( f ( t ) ) = 1 is called a delta series and a series f ( t ) has O ( f ( t ) ) = 0 is called an invertible series (see [5, 11]). By (16) and (17), we get e y t | x n = y n , and so e y t | p ( x ) = p ( y ) (see [5, 11]). For f ( t ) F and p ( x ) P , we have
f ( t ) = k = 0 f ( t ) | x k k ! t k , p ( x ) = k = 0 t k | p ( x ) k ! x k .
(19)
Let f 1 ( t ) , f 2 ( t ) , , f n ( t ) F . Then we see that
f 1 ( t ) f 2 ( t ) f n ( t ) | x n = i 1 + + i m = n ( n i 1 , , i m ) f 1 ( t ) | x i 1 f m ( t ) | x i m ,
(20)

where ( n i 1 , , i m ) = n ! i 1 ! i m ! (see [5, 11]).

For f ( t ) , g ( t ) F and p ( x ) P , it is easy to show that
f ( t ) g ( t ) | p ( x ) = f ( t ) | g ( t ) p ( x ) = g ( t ) | f ( t ) p ( x ) (see [11]) .
(21)
From (19), we can derive the following equation:
p ( k ) ( 0 ) = t k | p ( x ) and 1 | p ( k ) ( x ) = p ( k ) ( 0 ) .
(22)
By (22) we get
t k p ( x ) = p ( k ) ( x ) = d k p ( x ) d x k (see [5, 11]) .
(23)
Thus, from (23) we have
e y t p ( x ) = p ( x + y ) .
(24)
Let S n ( x ) be polynomials in the variable x with degree n, and let f ( t ) be a delta series and g ( t ) be an invertible series. Then there exists a unique sequence S n ( x ) of polynomials with g ( t ) f ( t ) k | S n ( x ) = n ! δ n , k ( n , k 0 ), where δ n , k is the Kronecker symbol. The sequence S n ( x ) is called the Sheffer sequence for ( g ( t ) , f ( t ) ) , which is denoted by S n ( x ) ( g ( t ) , f ( t ) ) . If S n ( x ) ( 1 , f ( t ) ) , then S n ( x ) is called the associated sequence for f ( t ) . If S n ( x ) ( g ( t ) , t ) , then S n ( x ) is called the Appell sequence for g ( t ) (see [5, 11]). For p ( x ) P , the following equations (25)-(27) are known in [5, 11]:
e y t 1 t | p ( x ) = 0 y p ( u ) d u ,
(25)
f ( t ) | x p ( x ) = t f ( t ) | p ( x ) = f ( t ) | p ( x ) ,
(26)
and
e y t 1 | p ( x ) = p ( y ) p ( 0 ) .
(27)
For S n ( x ) ( g ( t ) , f ( t ) ) , we have
h ( t ) = k = 0 h ( t ) | S k ( x ) k ! g ( t ) f ( t ) k , h ( t ) F ,
(28)
p ( x ) = k = 0 g ( t ) f ( t ) k | p ( x ) k ! S k ( x ) , p ( x ) P ,
(29)
f ( t ) S n ( x ) = n S n 1 ( x ) , f ( t ) | p ( α x ) = f ( α t ) | p ( x ) ,
(30)
1 g ( f ¯ ( t ) ) e y f ¯ ( t ) = k = 0 S k ( y ) k ! t k for all  y C ,
(31)
where f ¯ ( t ) is the compositional inverse of f ( t ) .
S n ( x + y ) = k = 0 n ( n k ) P k ( y ) S n k ( x ) = k = 0 n ( n k ) P k ( x ) S n k ( y ) ,
(32)

where P k ( y ) = g ( t ) S k ( y ) ( 1 , f ( t ) ) (see [5, 11]).

In contrast to the higher-order Euler polynomials, the more general higher-order Frobenius-Euler polynomials have never been studied in the context of umbral algebra and umbral calculus.

In this paper, we investigate some properties of polynomials related to Sheffer sequences. Finally, we derive some identities of higher-order Frobenius-Euler polynomials.

2 Associated sequences

Let p n ( x ) ( 1 , f ( t ) ) and q n ( x ) ( 1 , g ( t ) ) . Then, for n 1 , we note that
q n ( x ) = x ( f ( t ) g ( t ) ) n x 1 p n ( x ) (see [11]) .
(33)

Let us take f ( t ) = e a t 1 ( a 0 ). Then we see that f ( t ) = a e a t , f ¯ ( t ) = a 1 log ( t + 1 ) .

From (27), we can derive the associated sequence p n ( x ) for f ( t ) = e a t 1 as follows:
p n ( y ) = e y t | p n ( x ) = e y f ¯ ( t ) | x n = e y a log ( t + 1 ) | x n = ( t + 1 ) y a | x n = k = 0 ( y a k ) t k | x n = k = 0 n ( y a k ) n ! δ n , k = ( y a n ) n ! = ( y a ) n ,
(34)

where ( a ) n = a ( a 1 ) ( a n + 1 ) = Π i = 0 n 1 ( a i ) .

Therefore, by (34) we obtain, for n Z + ,
p n ( x ) = ( x a ) n ( 1 , e a t 1 ) .
We get the following:
p n + 1 ( x ) = x ( f ( t ) ) 1 p n ( x ) = a 1 x e a t p n ( x ) = ( x a ) ( x a a ) n = ( x a ) p n ( x a ) .
(35)
From (35), we can derive the equation
p n + 1 ( x ) = ( x a ) p n ( x a ) = ( x a ) ( x a a ) p n ( x 2 a ) = ( x a ) ( x a a ) ( x 2 a a ) p n ( x 3 a ) = = ( x a ) ( x a 1 ) ( x a 2 ) ( x a n ) .
(36)
By (19) we get
( x a ) n = k = 0 t k | ( x a ) n k ! x k = k = 0 n S 1 ( n , k ) a k x k
(37)
and
1 k ! t k | ( x a ) n = S 1 ( n , k ) a k ,
(38)

where S 1 ( n , k ) is the Stirling numbers of the first kind.

Therefore, by (37) and (38), we obtain the following theorem.

Lemma 1 For n , k 0 , we have
t k | ( x a ) n k ! = S 1 ( n , k ) a k .
From (31) we note that
k = 0 ( x a ) k k ! t k = e x a log ( 1 + t ) = ( t + 1 ) x a .
(39)
And by (32) we get
( x + y a ) n = k = 0 n ( n k ) ( x a ) k ( y a ) n k .
(40)
As is well known, the n th Frobenius-Euler polynomials are defined by the generating function to be
1 λ e t λ e x t = n = 0 H n ( x | λ ) t n n ! .
(41)
Thus, by (42) we see that H n ( x | λ ) ( e t λ 1 λ , t ) . So, we note that
e t λ 1 λ H n ( x | λ ) ( 1 , t ) .
(42)
It is easy to show that x n ( 1 , t ) (see Eq. (17)). Thus, from (42) we have
x n = x ( t t ) n x 1 ( e t λ 1 λ H n ( x | λ ) ) = 1 1 λ ( e t λ ) H n ( x | λ ) = 1 1 λ ( H n ( x + 1 | λ ) λ H n ( x | λ ) ) .
(43)

3 Frobenius-Euler polynomials of order α

From (1) and (31), we note that
H n ( α ) ( x | λ ) ( ( e t λ 1 λ ) α , t )
(44)
and
( 1 λ e t λ ) α x n = H n ( α ) ( x | λ ) for all  n 0 .
(45)
From (32), we have
H n ( α ) ( x + y ) = k = 0 n ( n k ) H k ( α ) ( y | λ ) x n k = k = 0 n ( n k ) H k ( α ) ( x | λ ) y n k .
(46)

Let us take the operator ( 1 λ e t λ ) β on both sides of (46).

Then we have
( 1 λ e t λ ) β H n ( α ) ( x + y | λ ) = ( 1 λ e t λ ) β ( 1 λ e t λ ) α ( x + y ) n = ( 1 λ e t λ ) α + β ( x + y ) n = H n ( α + β ) ( x + y | λ )
(47)
and by (46) we get
H n ( α + β ) ( x + y | λ ) = k = 0 n ( n k ) H k ( α ) ( y | λ ) ( 1 λ e t λ ) β x n k = k = 0 n ( n k ) H k ( α ) ( y | λ ) H n k ( β ) ( x | λ ) .
(48)

Therefore, by (48) we obtain the following proposition.

Proposition 2 For α , β C and n 0 , we have
H n ( α + β ) ( x + y | λ ) = k = 0 n ( n k ) H k ( α ) ( x | λ ) H n k ( β ) ( y | λ ) = k = 0 n ( n k ) H k ( α ) ( y | λ ) H n k ( β ) ( x | λ ) .
Thus, we have
e x t = n = 0 H n ( 0 ) ( x | λ ) t n n ! .
(49)
Thus, by (49) we get
H n ( 0 ) ( x | λ ) = x n .
(50)
Let us take β = α . Then, from Proposition 2, we have
( x + y ) n = k = 0 n ( n k ) H n k ( α ) ( x | λ ) H k ( α ) ( y | λ ) = k = 0 n ( n k ) H n k ( α ) ( y | λ ) H k ( α ) ( x | λ ) .
(51)

Therefore, by (51) we obtain the following corollary.

Corollary 3 For n 0 , we have
( x + y ) n = k = 0 n ( n k ) H n k ( α ) ( x | λ ) H k ( α ) ( y | λ ) = k = 0 n ( n k ) H n k ( α ) ( y | λ ) H k ( α ) ( x | λ ) .
In the special case, y = 0 , we have
x n = k = 0 n ( n k ) H n k ( α ) ( x | λ ) H k ( α ) ( λ ) .
Let α N . We get
n = 0 H n ( α ) ( λ ) n ! t n = ( e t λ 1 λ ) α = 1 ( 1 λ ) α l = 0 α ( α l ) ( 1 ) α l λ α l e l t = n = 0 ( 1 ( 1 λ ) α l = 0 α ( α l ) ( 1 ) α l λ α l l n ) t n n ! .
(52)
Thus, from (52) we have
H n ( α ) ( λ ) = 1 ( 1 λ ) α l = 0 α ( α l ) ( 1 ) α l λ α l l n = 1 ( 1 λ ) α λ α 0 n = α ! ( 1 λ ) α λ α 0 n α ! = α ! ( 1 λ ) α S ( n , α | λ ) .
(53)

Therefore, by (51), (52) and (53), we obtain the following theorem.

Theorem 4 For α N and n 0 , we have
( 1 λ ) α α ! x n = k = 0 n ( n k ) H n k ( α ) ( x | λ ) S ( k , α | λ ) .
From (19), we have
x n = k = 0 n ( e t λ 1 λ ) α t k | x n k ! H k ( α ) ( x | λ ) = k = 0 n 1 k ! ( e t λ 1 λ ) α | t k x n H k ( α ) ( x | λ ) = k = 0 n ( n k ) ( e t λ 1 λ ) α | x n k H k ( α ) ( x | λ )
(54)
and
( e t λ 1 λ ) α | x n k = j = 0 H j ( α ) ( λ ) j ! t j | x n k = j = 0 H j ( α ) ( λ ) j ! δ n k , j ( n k ) ! = H n k ( α ) ( λ ) .
(55)
By (54) and (55), we also get
x n = k = 0 n ( n k ) H k ( α ) ( x | λ ) H n k ( α ) ( λ ) .

4 Further remark

Let us take a = 1 in (34). Then we have ( x ) n ( 1 , f ( t ) = e t 1 ) , x n ( 1 , g ( t ) = t ) .

For n 1 , by (33) we get
x n = x ( e t 1 t ) n x 1 ( x ) n = x ( e t 1 t ) n ( x 1 ) n 1 = x l = 0 n ! ( l + n ) ! S 2 ( l + n , n ) t l ( x 1 ) n 1 ,
(56)

where S 2 ( m , n ) is the Stirling numbers of the second kind.

From (56) we have
( x + 1 ) n + 1 = ( x + 1 ) l = 0 n ( n + 1 ) ! ( l + n + 1 ) ! S 2 ( l + n + 1 , n + 1 ) t l ( x ) n ,
(57)
where
( x ) n = l = 0 n S 1 ( n , k ) x k .
(58)
Thus, by (58) we get
t l ( x ) n = d l d t l ( x ) n = k = l n S 1 ( n , k ) ( k ) l x k l .
(59)
From (57) and (59), we can derive the following equation:
( x + 1 ) n = l = 0 n ( n + 1 ) ! ( l + n + 1 ) ! S 2 ( l + n + 1 , n + 1 ) k = l n S 1 ( n , k ) ( k ) l x k l = l = 0 n m = 0 n l ( l + m l ) ( n + l + 1 l ) S 2 ( l + n + 1 , n + 1 ) S 1 ( n , l + m ) x m = m = 0 n { l = 0 n m ( l + m l ) ( n + l + 1 l ) S 2 ( l + n + 1 , n + 1 ) S 1 ( n , l + m ) } x m
(60)
and
( x + 1 ) n = l = 0 n ( n l ) x l .
(61)

Therefore, by (60) and (61), we obtain the following lemma.

Lemma 5 For 0 m n , we have
( n m ) = l = 0 n m ( l + m l ) ( n + l + 1 l ) S 2 ( l + n + 1 , n + 1 ) S 1 ( n , l + m ) .
Let α = 1 . Then we write H n ( 1 ) ( x | λ ) = H n ( x | λ ) . From (34), we note that
( x ) n ( 1 , e t 1 ) .
(62)
Thus, by (19) and (62), we get
H n ( x | λ ) = k = 0 ( e t 1 ) k | H n ( x | λ ) k ! ( x ) k = H n ( λ ) + k = 1 ( e t 1 ) k | H n ( x | λ ) k ! ( x ) k .
(63)
For k 1 , we have
( e t 1 ) k | H n ( x | λ ) = l = 0 n ( n l ) H n l ( λ ) ( e t 1 ) k | x l .
(64)
From (9), we have
1 k ! ( e t 1 ) k | x l = S 2 ( l , k ) .
(65)

Therefore, by (63), (64) and (65), we obtain the following theorem.

Theorem 6 For n 0 , we have
H n ( x | λ ) = H n ( λ ) + k = 1 n l = 0 n ( n l ) H n l ( λ ) S 2 ( l , k ) ( x ) k = H n ( λ ) + k = 1 n l = 0 n m = 0 k ( n l ) H n l ( λ ) S 2 ( l , k ) S 1 ( k , m ) x m .
From the recurrence formula of the Appell sequence, we note that
H n + 1 ( α ) ( x | λ ) = ( x α e t e t λ ) H n ( α ) ( x | λ ) = x H n ( α ) ( x | λ ) α e t e t λ H n ( α ) ( x | λ ) = x H n ( α ) ( x | λ ) α ( 1 λ ) 1 λ e t λ H n ( α ) ( x + 1 ) = x H n ( α ) ( x | λ ) α ( 1 λ ) H n ( α + 1 ) ( x + 1 ) .
(66)

Therefore, by (66) we obtain the following theorem.

Theorem 7 For n 0 , we have
H n + 1 ( α ) ( x | λ ) = x H n ( α ) ( x | λ ) α ( 1 λ ) H n ( α + 1 ) ( x + 1 ) .

Declarations

Acknowledgements

Dedicated to Professor Hari M Srivastava.

The authors express their sincere gratitude to the referees for their valuable suggestions and comments. This paper is supported in part by the Research Grant of Kwangwoon University in 2013.

Authors’ Affiliations

(1)
Department of Mathematics, Sogang University
(2)
Department of Mathematics, Kwangwoon University
(3)
Division of General Education, Kwangwoon University
(4)
Department of Mathematics Education, Kyungpook National University

References

  1. Araci S, Acikgoz M: A note on the Frobenius-Euler numbers and polynomials associated with Bernstein polynomials. Adv. Stud. Contemp. Math. 2012, 22: 399-406.MATHMathSciNetGoogle Scholar
  2. Can M, Cenkci M, Kurt V, Simsek Y: Twisted Dedekind type sums associated with Barnes’ type multiple Frobenius-Euler l -functions. Adv. Stud. Contemp. Math. 2009, 18: 135-160.MATHMathSciNetGoogle Scholar
  3. Carlitz L: The product of two Eulerian polynomials. Math. Mag. 1963, 36: 37-41. 10.2307/2688134MATHMathSciNetView ArticleGoogle Scholar
  4. Kim T: Identities involving Frobenius-Euler polynomials arising from non-linear differential equations. J. Number Theory 2012, 132(12):2854-2865. 10.1016/j.jnt.2012.05.033MATHMathSciNetView ArticleGoogle Scholar
  5. Kim DS, Kim T: Some new identities of Frobenius-Euler numbers and polynomials. J. Inequal. Appl. 2012., 2012: Article ID 307Google Scholar
  6. Kim T: An identity of the symmetry for the Frobenius-Euler polynomials associated with the fermionic p -adic invariant q -integrals on Z p . Rocky Mt. J. Math. 2011, 41: 239-247. 10.1216/RMJ-2011-41-1-239MATHView ArticleGoogle Scholar
  7. Kim T: On explicit formulas of p -adic q - L -functions. Kyushu J. Math. 1994, 48: 73-86. 10.2206/kyushujm.48.73MATHMathSciNetView ArticleGoogle Scholar
  8. Kim T, Choi J: A note on the product of Frobenius-Euler polynomials arising from the p -adic integral on Z p . Adv. Stud. Contemp. Math. 2012, 22: 215-223.MATHGoogle Scholar
  9. Kim T: A note on q -Bernstein polynomials. Russ. J. Math. Phys. 2011, 18(1):73-82. 10.1134/S1061920811010080MATHMathSciNetView ArticleGoogle Scholar
  10. Kim DS, Kim T, Kim YH, Dolgy DV: A note on Eulerian polynomials associated with Bernoulli and Euler numbers and polynomials. Adv. Stud. Contemp. Math. 2012, 22(3):379-389.MATHMathSciNetGoogle Scholar
  11. Roman S: The Umbral Calculus. Dover, New York; 2005.Google Scholar
  12. Kim DS, Kim T, Lee S-H, Rim S-H: Frobenius-Euler polynomials and umbral calculus in the p -adic case. Adv. Differ. Equ. 2012., 2012: Article ID 222Google Scholar
  13. Kim DS, Kim T: Euler basis, identities, and their applications. Int. J. Math. Math. Sci. 2012., 2012: Article ID 343981Google Scholar
  14. Rim S-H, Joung J, Jin J-H, Lee S-J: A note on the weighted Carlitz’s type q -Euler numbers and q -Bernstein polynomials. Proc. Jangjeon Math. Soc. 2012, 15: 195-201.MATHMathSciNetGoogle Scholar
  15. Ryoo CS: A note on the Frobenius-Euler polynomials. Proc. Jangjeon Math. Soc. 2011, 14: 495-501.MATHMathSciNetGoogle Scholar
  16. Simsek Y, Yurekli O, Kurt V: On interpolation functions of the twisted generalized Frobenius-Euler numbers. Adv. Stud. Contemp. Math. 2007, 15: 187-194.MATHMathSciNetView ArticleGoogle Scholar
  17. Shiratani K, Yamamoto S: On a p -adic interpolation function for the Euler numbers and its derivatives. Mem. Fac. Sci., Kyushu Univ., Ser. A, Math. 1985, 39: 113-125.MATHMathSciNetGoogle Scholar

Copyright

© Kim et al.; licensee Springer 2013

This article is published under license to BioMed Central Ltd. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.